Exploring Global Research Trends in Sports Tourism Policy: Formulating Indonesia's future policies - Kisman Karinda; Tawakkal Baharuddin; Kittisak Jermsittiparsert (Journal of Government and Civil Society, 2024)
Issues regarding tourism have been integrated with aspects of sport and are now known as sport tourism. This research aims to evaluate published documents available globally to serve as a guide in understanding this context correctly and initiating policies needed by the Indonesian government. The method used is a bibliometric analysis approach with data sources from the Scopus database. Analysis tools use Vosviewer and Nvivo 12 Plus. This study finds that global research trends on sport tourism policy have influenced the interests of researchers worldwide. This is proven by the high number of recently published documents. Several research themes require further exploration, including tourist destinations and tourist industry. This can be a basis for future research in building perspectives and unravelling other complexities. The implications of these findings also contribute to Indonesia in formulating future policies. Several vital aspects that can be a stepping stone for the Indonesian government are promoting tourism destinations, organizing international sporting events, developing infrastructure, and empowering local communities as essential elements in creating a sustainable sports tourism ecosystem. Responsiveness to global changes is also a critical point that needs to be considered.Isu tentang pariwisata telah diintegrasikan dengan aspek olahraga dan saat ini dikenal dengan istilah sport tourism. Tujuan penelitian ini untuk mengevaluasi dokumen publikasi yang tersedia secara global untuk dijadikan pedoman dalam memahami konteks ini secara baik, sekaligus menginisiasi kebijakan yang diperlukan pemerintah Indonesia. Metode yang digunakan yaitu dengan pendekatan analisis bibliometrik dengan sumberdata dari database Scopus. Alat analisis menggunakan Vosviewer dan Nvivo 12 Plus. Studi ini menemukan bahwa tren penelitian global tentang kebijakan sport tourism telah memengaruhi minat peneliti di seluruh dunia. Itu dibuktikan dengan tingginya jumlah dokumen publikasi baru-baru ini. Terdapat beberapa tema penelitian yang memerlukan eksplorasi lanjutan di antaranya yaitu tourist destination dan tourist industry. Hal itu dapat menjadi dasar bagi penelitian masa depan dalam mebangun perspektif dan mengurai kompleksitas lainnya. Implikasi dari temuan ini juga berkontribusi bagi Indonesia dalam merumuskan kebijakan masa depan. Beberapa aspek kunci yang dapat menjadi pijakan untuk pemerintah Indonesia yaitu mempertimbangkan promosi destinasi pariwisata, penyelenggaraan acara olahraga internasional, pengembangan infrastruktur, dan pemberdayaan masyarakat lokal menjadi elemen penting dalam menciptakan ekosistem sport tourism yang berkelanjutan. Responsif terhadap perubahan global juga menjadi poin kritis yang perlu diperhatikan.